A Systematic Overview of Issues for Developing EFL Learners' Oral English Communication Skills - Prodhan Mahbub Ibna Seraj; Habil Hadina (National Research University Higher School of Economics, 2021)
The objective of this systematic review is to present a critical overview of current studies to explore issues such as the factors causing EFL learners' poor oral performance and the teaching and assessment methods of oral English communication skills (OECSs) for developing tertiary level learners' OECSs in EFL contexts. For this purpose, 51 empirical studies of the 2907 retrieved from SpringerLink, SCOPUS, Web of Science, and the Google Scholar database that were published between 2010 and 2019 in different EFL contexts were analyzed. This study followed the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidelines and was analyzed thematically using NVIVO 12, followed by the Mendeley reference management software. Studies that were conducted in native English contexts and non-empirical studies were excluded from consideration for this study. The findings showed that the environmental factor was the primary factor for learners' poor OECS performance in EFL contexts. For the method of teaching and assessment of learners' OECSs, the use of technology is rapidly increasing in different EFL contexts. This study suggests some implications for both future researchers and academics for developing EFL learners' oral English communication skills dealing with environmental, psychological, and linguistic factors along with teaching and learning resources at the tertiary level in EFL contexts.